Trait-related functional changes in understory forest community after invasion are driven by complementarity rather than displacement - Petri, Laís; Ibáñez, Inés (Frontiers in Ecology and Evolution, 2024)
Forests support a variety of functions essential for the provisioning of ecosystem services. However, invasive plants can disrupt forest functioning, particularly in temperate forest understories that commonly experience invasive plant encroachment, by altering communitylevel trait distributions. Invasive plants, frequently characterized by acquisitive traits such as higher specific leaf area and nitrogen content, may either outcompete native species with different trait values (displacement), or add trait values to the existing community (complementarity). Therefore, complementarity may still allow restoration of the original community function by removing invasive species, and consequently the added provision of function when compared to the natives, but displacement may not. While understanding which process occurs is critical in managing ecosystem functionality, little is known about the impact of invasion on the co-occurring native community trait distributions. To address this knowledge gap, we leveraged survey data on temperate forest understories that varied in their degree of invasion (i.e., gradient of invasion). We calculated the community-weighted mean of three leaf traits: leaf nitrogen, specific leaf area, and leaf dry matter contenttraits strongly linked to invasion, sensitive to environmental changes, and that affect ecosystem functions. Our findings show that increasing invasion had a significant positive effect on total (native and invasive) community leaf nitrogen, but did not alter native community trait distributions. This suggests that potential impacts on ecosystem functions, such as increased primary productivity and nitrogen cycling, would be primarily driven by trait complementarity and not displacement. We did not find any significant differences in the total or native communities with respect to specific leaf area or leaf dry matter content. Differentiating trait displacement from trait complementarity contributes to our understanding of how invasion affects functionality of understory plant communities in forests. Additionally, it provides a valuable framework to facilitate evidencebased decisions for the management of ecosystem functionality.